Advancing high-resolution musculoskeletal ultrasound: A histology- and anatomy-driven approach for enhanced shoulder imaging. Part I: Posterior and coronal shoulder - Tamborrini Giorgio; Micheroli Raphael; Ricci Vincenzo; Becciolini Marco; Garcia-Pompermayer Mario; Gonzalo Andres Serrano Belmar; Müller-Gerbl Magdalena; Margenfeld Felix (Journal of Ultrasonography)
Ultrasound is a reliable imaging modality for diagnosing and assessing musculoskeletal disorders. Recent advancements in ultrasound technology have substantially improved image resolution, enabling the visualization of anatomic structures on a near-microscopic level. However, existing guidelines for standardized shoulder ultrasound primarily rely on earlier machine models and settings that may not harness the full potential of these high-resolution imaging capabilities. This article provides a simple and systematic guide to high-resolution sonography of the shoulder using anatomical and histological images from cadavers for comparison. International standard techniques are considered, and images were obtained using modern equipment. This two-article series systematically shows the examination and normal findings, presenting first the posterior, then frontal, then further anterior, followed by lateral and, optionally, the axillary examination. In this article, the focus is on the posterior and coronal shoulder.